2023
DOI: 10.4155/tde-2023-0131
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Exosomes: A Promising Vehicle in Cancer Therapy

Farkhondeh Pooresmaeil,
Sahar Andi,
Behnam Hasannejad-Asl
et al.

Abstract: During the past few decades, researchers have attempted to discover an effective treatment for cancer. Exosomes are natural nanovesicles released by various cells and play a role in communication between cells. While natural exosomes have high clinical potential, their inherent limitations have prompted researchers to design exosomes with improved therapeutic properties. To achieve this purpose, researchers have undertaken exosome engineering to modify the surface properties or internal composition of exosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 125 publications
0
1
0
Order By: Relevance
“…To address those concerns, natural exosomes can be modified using biotechnology based on the clinical application requirements, resulting in the so-called engineered exosomes. 31 Compared with the natural exosomes, many experiments have shown that the engineered exosomes can enhance drug efficiency, 32,33 improve targeting ability, 34,35 and increase resistance to the body clearance rate. 36,37…”
Section: Introductionmentioning
confidence: 99%
“…To address those concerns, natural exosomes can be modified using biotechnology based on the clinical application requirements, resulting in the so-called engineered exosomes. 31 Compared with the natural exosomes, many experiments have shown that the engineered exosomes can enhance drug efficiency, 32,33 improve targeting ability, 34,35 and increase resistance to the body clearance rate. 36,37…”
Section: Introductionmentioning
confidence: 99%